Associations between [18F]AV1451 tau PET and CSF measures of tau pathology in a clinical sample. (23rd January 2018) - La Joie, Renaud; Bejanin, Alexandre; Fagan, Anne M.; Ayakta, Nagehan; Baker, Suzanne L.; Bourakova, Viktoriya; Boxer, Adam L.; Cha, Jungho; Karydas, Anna; Jerome, Gina; Maass, Anne; Mensing, Ashley; et al.
Abstract : Objective: To assess the relationships between fluid and imaging biomarkers of tau pathology and compare their diagnostic utility in a clinically heterogeneous sample. Methods: Fifty-three patients (28 with clinical Alzheimer disease [AD] and 25 with non-AD clinical neurodegenerative diagnoses) underwent β-amyloid (Aβ) and tau ([ 18 F]AV1451) PET and lumbar puncture. CSF biomarkers (Aβ42, total tau [t-tau], and phosphorylated tau [p-tau]) were measured by multianalyte immunoassay (AlzBio3). Receiver operator characteristic analyses were performed to compare discrimination of Aβ-positive AD from non-AD conditions across biomarkers. Correlations between CSF biomarkers and PET standardized uptake value ratios (SUVR) were assessed using skipped Pearson correlation coefficients. Voxelwise analyses were run to assess regional CSF–PET associations. Results: [ 18 F]AV1451-PET cortical SUVR and p-tau showed excellent discrimination between Aβ-positive AD and non-AD conditions (area under the curve 0.92–0.94; ⩽0.83 for other CSF measures), and reached 83% classification agreement. In the full sample, cortical [ 18 F]AV1451 was associated with all CSF biomarkers, most strongly with p-tau ( r = 0.75 vs 0.57 for t-tau and −0.49 for Aβ42 ). When restricted to Aβ-positive patients with AD, [ 18 F]AV1451 SUVR correlated modestly with p-tau and t-tau (both r = 0.46) but not Aβ42 ( r = 0.02). On voxelwise analysis, [ 18 F]AV1451 correlated with CSF p-tau in temporoparietal cortices and with t-tau in medial prefrontal regions. Within AD, Mini-Mental State Examination scores were associated with [ 18 F]AV1451-PET, but not CSF biomarkers. Conclusion: [ 18 F]AV1451-PET and CSF p-tau had comparable value for differential diagnosis. Correlations were robust in a heterogeneous clinical group but attenuated (although significant) in AD, suggesting that fluid and imaging biomarkers capture different aspects of tau pathology. Classification of evidence: This study provides Class III evidence that, in a clinical sample of patients with a variety of suspected neurodegenerative diseases, both CSF p-tau and [ 18 F]AV1451 distinguish AD from non-AD conditions.